U.S. Paralympic Hopeful's Athletic Identity and How It Has Been Affected by the Sport Disruption of COVID-19 - Hu, Tiao; Mendoza, Mathew; Cabador, Joy Viray; Cottingham, Michael (Frontiers in Sports and Active Living, 2021)
The purpose of this study was to explore the status of Paralympic hopefuls’ athletic identity and how it has been impacted by COVID-19. Researchers conducted in-depth semi-structured interviews that explored the experiences of 29 Paralympic hopefuls who compete in eleven different Paralympic sports. A thematic analysis yielded two superordinate themes: a) Prominent athletic identity, multiplicity over exclusivity; b) Various Impact on AI: Mental adaptation helps overcome the lack of sport participation. Participants in this study possessed prominent strong athletic identities from the benefits of sport participation. Their prioritized athletic role still remains despite setbacks due to the pandemic. However, athletes identified with multiple roles rather than an exclusive athletic identity during COVID-19. As for the impacts on identity, the severity of challenges are determined by the mindset of the athletes. All of the athletes experienced a decreased amount of time and physical participation in their sport. Paralympians whose sole focus was on the loss of physical participation were impacted the most. Athletes who felt unchallenged did so because of their mental adaptation. Through a positive outlook and mentality, athletes were able to effectively cope and not dwell on the negative aspects brought on by the pandemic. In conclusion, having strong AI did not necessarily result in negative identity impacted by COVID-19. In addition, COVID-19 did not challenge those who do not possess a strong AI. More importantly, Paralympians’ mindset of how they view and interpret their AI is crucial to how the individual’s AI is affected by COVID-19.